2011
DOI: 10.1002/adma.201190157
|View full text |Cite
|
Sign up to set email alerts
|

Graphene: Evidence for a New Two‐Dimensional C4H‐Type Polymer Based on Hydrogenated Graphene (Adv. Mater. 39/2011)

Abstract: A partially hydrogenated graphene sheet with C4H stoichiometry where the hydrogen atoms self‐assemble to a para‐type chemisorption pattern in which the hydrogen atoms are located at opposite sides of the hexagons is reported. , Danny Haberer, Hermann Sachdev, Stephan Irle, Alexander Grüneis, and co‐workers describe the synthesis and in situ characterization by pho‐toemission spectroscopy of this new compound.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…At zero doping the C 8 X 2 structures are by several 100 meV per atom more favorable than the X[1:1] or X[1:0] structures. This finding is in line with the tendency of H and F to aggregate when adsorbed on graphene 2,23,24 .…”
supporting
confidence: 87%
See 1 more Smart Citation
“…At zero doping the C 8 X 2 structures are by several 100 meV per atom more favorable than the X[1:1] or X[1:0] structures. This finding is in line with the tendency of H and F to aggregate when adsorbed on graphene 2,23,24 .…”
supporting
confidence: 87%
“…Previous DFT calculations showed that the C 8 X 2 -structures (Fig. 1C shaded area) correspond to the upper concentration limit for H/F single side adsorption on graphene 2,23 . We thus compare E ads for the ordered C 8 X 2 structures to graphene with 10% adsorbed hydrogen and fluorine adatoms 1 in fully random (X[1:1], Fig.…”
mentioning
confidence: 71%
“…Large adatoms prefer the hollow site position when added to a graphene sheet [7] while small atoms such as hydrogen prefer the top site position [5]. Therefore, implicit assumption of s-wave orbital structure for the impurity atom itself is only feasible for top site positions.…”
Section: Internal Structure Of the Impurity Orbital In Hollow Site Ad...mentioning
confidence: 99%
“…For example, two-dimensionality allows for tuning the carrier type and density by a gate voltage. On the one hand, the flat structure of graphene allows us to add/substitute various atoms on graphene [5]. On the other hand, the two-dimensional structure further allows us to conveniently remove some of the carbon atoms and create vacancies.…”
Section: Introductionmentioning
confidence: 99%